The creature of the pines - Gidwitz, Adam (Gidwitz, Adam. Unicorn Rescue Society, 2018)
After encountering a Jersey Devil while on a field trip to the Pine Barrens, Elliot and his new friend Uchenna help their weird teacher Professor Fauna rescue the mythological creature from a pair of greedy billionaire brothers.